2018
DOI: 10.17509/eh.v10i1.8396
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Hidden Curriculum Pada Mata Pelajaran Pendidikan Al-Islam Di Sd Muhammadiyah Wirobrajan I Yogyakarta

Abstract: Abstract:. The problem that often arise in the study is the lack of understanding of the hidden curriculum so the teacher does not know the positive impact of the hidden curriculum activity itself, despite the fact that the hidden curriculum activities are often carried out in the learning process. This study was aimed to describe the hidden curriculum implementation strategy on educational subjects of Al-Islam in SD Muhammadiyah I Yogyakarta Wirobrajan academic year 2017/2018. The method used in this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…This means that there is a significant or real difference between students" understanding of the importance of national insight material: The results of this study in accordance with Widya's research, suggest that the application of the development of anti-corruption materials in the hidden curriculum is very effective and feasible 21 . Likewise, with the results of research conducted by Ika Maryani and Fitria which revealed that the implementation of the hidden curriculum in the subject of al-Islam Education was able to provide positive habits 22 . These results are also reinforced by the findings of M. Slamet who argued that the development of a hidden curriculum in the subject matter was able to increase student understanding 23 .…”
Section: Figure 3 Trial Results (Stage 1)mentioning
confidence: 89%
“…This means that there is a significant or real difference between students" understanding of the importance of national insight material: The results of this study in accordance with Widya's research, suggest that the application of the development of anti-corruption materials in the hidden curriculum is very effective and feasible 21 . Likewise, with the results of research conducted by Ika Maryani and Fitria which revealed that the implementation of the hidden curriculum in the subject of al-Islam Education was able to provide positive habits 22 . These results are also reinforced by the findings of M. Slamet who argued that the development of a hidden curriculum in the subject matter was able to increase student understanding 23 .…”
Section: Figure 3 Trial Results (Stage 1)mentioning
confidence: 89%
“…Hasil menunjukkan bahwa terdapat perubahan kemampuan literasi siswa setelah diadakannya GLS di sekolah yang diteliti, namun terdapat beberapa faktor penghambat dan pendukung yang dapat membuat program tersebut diselenggarakan secara berkesinambungan dan efektif (Hidayat et al, 2018;Khofifah & Ramadan, 2021). Faktor yang memengaruhi diantaranya komitmen guru dan orang tua, serta sarana dan prasarana yang memadai (Maryani & Maryam, 2017).…”
Section: Pendahuluanunclassified
“…Selain itu, program literasi sekolah dapat memperkuat budaya literasi. Pernyataan tersebut selaras dengan hasil evaluasi pada Gerakan Literasi Sekolah (GLS) di sekolah lain yaitu SD Muhammadiyah Wirobrajan 3 yang berdampak munculnya budaya literasi di siswa yang konsisten (Maryani & Maryam, 2017).…”
Section: Dampak Program Penguatan Literasi Pada Hasil Asesmen Kompete...unclassified
“…Selain itu, Muhammadiyah telah memainkan berbagai peran dalam berdakwah dan membangun negeri ini selama lebih dari satu abad, mengasuh umat. Banyak bidang tabligh yang harus ditangani Muhammadiyah, serta berbagai persoalan dakwah yang dihadapi baik lokal maupun internasional (Maryani & Maryam, 2017). Pusat Kesehatan Semesta (PKU), Rumah Sakit Muhammadiyah maupun Balai Pengobatan adalah salah satu dari sekian banyak amal yang didirikan oleh organisasi ini di berbagai bidang, termasuk pendidikan dari sekolah dasar hingga akademi besar, bidang ekonomi yakni koperasi.…”
Section: Pembahasanunclassified